Transforming Food Systems for a Rising India - Pingali, Prabhu; Aiyar, Anaka; Abraham, Mathew; Rahman, Andaleeb (Palgrave Studies in Agricultural Economics and Food Policy, 2019)
'This book... brings together high quality research, real world pragmatism and an understanding of the politics of Indian food systems.' - Lawrence Haddad, Executive Director, GAIN and 2018 World Food Prize Laureate '[The authors] have done a masterful job of [demonstrating] paradoxes of India's rapid economic growth concurrently with... persistent poverty, food insecurity and... a triple burden of malnutrition.' - Uma Lele, President-Elect International Association of Agricultural Economics (IAAE) 'Using a broad food systems approach, this book presents [a]... comprehensive analysis of the Indian food and agricultural system and its interaction with climate change, nutrition and health.' - Per Pinstrup-Andersen, Professor Emeritus, Cornell University and 2001 World Food Prize Laureate This open access book examines India's economic development, agricultural production, and nutrition through the lens of a "Food Systems Approach (FSA)." Despite economic progress, regional inequality, food insecurity and malnutrition persist. Simultaneously, recent trends in obesity and micro-nutrient deficiency indicate a future public health crisis. This book explores the challenges and opportunities to achieve a nutrition-secure future through diversified production systems, improved health and hygiene and greater individual capability to access a balanced diet. Within the context of developing countries, they highlight India's status as an outlier regarding high levels of stunting and global trends in obesity. This book discusses the policy and institutional interventions needed to promote a nutrition-sensitive food system and the multi-sectoral strategies needed to address malnutrition in India. Prabhu Pingali is Professor of Applied Economics and Founding Director of the Tata-Cornell Institute for Agriculture and Nutrition (TCI) at CornellUniversity. Anaka Aiyar is Post-Doctoral Associate with the Tata-Cornell Institute for Agriculture and Nutrition (TCI), Cornell University. Mathew Abraham is Assistant Director of the Tata-Cornell Institute for Agriculture and Nutrition (TCI), Cornell University. Andaleeb Rahman is Post-Doctoral Associate at the Tata-Cornell Institute for Agriculture and Nutrition (TCI), Cornell University.